Peran Polri Dalam Pemberantasan Perusakan Hutan - Risky Caniago; Nurul Mutia Baba; Habibul Ghufron; Saharudin Saharudin; Fitrisia Madina (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Forests are natural resources that are renewable and contribute to the state in the form of taxes and people's welfare from the value of existing logs. What is the judicial process for violations of forest law. What are the obstacles to law enforcement against crimes in the forestry sector. The methodology is normative legal research which is legal research conducted by examining literature.The results of the research show that the process of investigating crimes in the forestry sector is regulated specifically, namely that it is carried out by Investigating Officers of Civil Servants within the Ministry/Forestry Service both at the central and regional levels. In addition to special investigators, there are other law enforcement officials who also have the authority to investigate crimes in the forestry sector, namely investigators from the National Police, the Attorney General's Office and the Navy, and law enforcement against crimes in the forestry sector experiences several obstacles, both juridical in nature, originating from regulations the laws governing forestry, namely the formulation of forestry offenses cannot reach the intellectual perpetrators of crimes in the forestry sector. In conclusion, the process of investigating crimes in the forestry sector is regulated specifically, namely to be carried out by Investigating Officers of Civil Servants within the Ministry/Forestry Service both at the central and regional levels. Law enforcement against crimes in the forestry sector experiences several obstacles, both of a juridical nature, namely the formulation of forestry offenses cannot reach the intellectual perpetrators of crimes in the forestry sector.